Peran Kimia Hijau dalam Membangun Pendidikan Etika - Annisa Mamluaturrahmatika; Suwardi; Nurfina Aznam (Jurnal Penelitian Pendidikan IPA, 2024)
This is very important in growing students' environmental awareness through integrating green chemistry in learning as one of the efforts to protect the environment and reduce environmental pollution. Chemistry learning through green chemistry education has great potential in developing ethics as a method for solving environmental problems. Green chemistry has 12 principles that are expected to address pressing environmental problems such as pollution, waste management, energy shortages, and workplace safety and security. This research type is descriptive. As much as 77% of the average students in this study with a good enough category indicates that green chemistry has an important role in building chemistry ethics. Ethics is used in general to describe human attitudes towards a problem. Ethics education in chemistry with a green chemistry perspective is carried out by teaching and training integrated into courses with the hope that it will become ethical habituation that will build chemistry ethics.